2018
DOI: 10.1088/1361-6560/aac1ad
|View full text |Cite
|
Sign up to set email alerts
|

Y-90 SPECT ML image reconstruction with a new model for tissue-dependent bremsstrahlung production using CT information: a proof-of-concept study

Abstract: While the yield of positrons used in Y-90 PET is independent of tissue media, Y-90 SPECT imaging is complicated by the tissue dependence of bremsstrahlung photon generation. The probability of bremsstrahlung production is proportional to the square of the atomic number of the medium. Hence, the same amount of activity in different tissue regions of the body will produce different numbers of bremsstrahlung photons. Existing reconstruction methods disregard this tissue-dependency, potentially impacting both qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…According to the visual evaluations and ANOVA/ Tukey test results, it was concluded that energy window of 90-110 keV is the optimal energy window while 60-400 keV energy ranges show the lowest image quality for Y-90 bremsstrahlung imaging. These ranges are consistent with other investigations related energy window optimization with medium energy collimator [6,8,12,13]. Namely, due to the Y-90 Bremsstrahlung energy spectrum has large numbers of low-energy photons, it is concluded that 50-100 keV energy window is the most proper energy window when using the medium energy collimator [23].…”
Section: Optimal Imaging Conditions For Planar Imagessupporting
confidence: 90%
See 2 more Smart Citations
“…According to the visual evaluations and ANOVA/ Tukey test results, it was concluded that energy window of 90-110 keV is the optimal energy window while 60-400 keV energy ranges show the lowest image quality for Y-90 bremsstrahlung imaging. These ranges are consistent with other investigations related energy window optimization with medium energy collimator [6,8,12,13]. Namely, due to the Y-90 Bremsstrahlung energy spectrum has large numbers of low-energy photons, it is concluded that 50-100 keV energy window is the most proper energy window when using the medium energy collimator [23].…”
Section: Optimal Imaging Conditions For Planar Imagessupporting
confidence: 90%
“…For example, it is reported that the fraction of detected photons undergoing septal penetration for a 400-450 keV window is much larger than for a 100-150 keV window [24]. It is reported that energy window conditions with wider ranges of energy width (60-400 keV) cause higher FWHM, as a result of more unexpected photons [8]. As a summary of the above, effect of energy region and energy-window width on the image quality parameters found in this study can be seen from figure 11.…”
Section: Optimal Imaging Conditions For Planar Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consideration is the degradation in spatial resolution because of the finite distance between the location of the 90 Y decay and the location where the external bremsstrahlung photons are generated, akin to positron range effects in PET. A further complication is that the bremsstrahlung yield and energy spectrum is tissue dependent (Lim et al , 2018c), but this effect is not significant when imaging homogenous regions such as the liver.…”
Section: Quantification Of Activity In Source Regions For Dosimetrymentioning
confidence: 99%
“…Quantitative imaging of bremsstrahlung radiation requires a good combination of radionuclide collimator and gamma cameras [17][18][19][20][21][22]. For quantitative imaging of gammas, combined SPECT with xray computed tomography (SPECT/CT) will add great benefits for quantification [23]. For Tb-149, PET/CT will be a quantitative imaging tool by the same token with its position emission, a rarity for alpha-emitters [24].…”
Section: Imageable Signals From Alpha-emitting Radionuclidesmentioning
confidence: 99%